AB0623 Psychological Profile of Patients with Sjogren's Syndrome – Associations with Disease Activity. (9th June 2015) - Milic, V.; Grujic, M.; Radunovic, G.; Barisic, J.; Duisin, D.; Damjanov, N.
Abstract : Background: Psychological profiles of patients with Sjogren's syndrome (SS) can influence severity of symptoms of dryness, pain, fatigue and fibromyalgia. We assume that treatment of the disease manifestations can be improved when the psychological heterogeneity of patients is taken into account. Objectives: To determine the spectrum of psychological features in SS patients and to assess the association of psychological profiles with disease activity. Methods: Seventy patients with confirmed SS by AECG criteria (mean age 51, 3 years, mean disease duration 4.7 years) and thirty-two healthy controls (mean age 50.3 years) participated in our study. All participants were females who provided written informed consent. The disease activity was measured by EULAR SS disease activity index (ESSDAI). All participants filled the self-reported questionnaire which addresses demographic characteristics (age, educational level, occupational status, residence and comorbidity). The second part consisted of the NEO Personality Inventory-Revised (NEO-PI-R) - a 240-item measure of the Big Five personality profiles: Neuroticism (N), Extraversion (E), Openness to Experience (O), Agreeableness (A) and Conscientiousness C. Items are answered on a 5-point Likert scale, ranging from strong disagreement to strong agreement. Level of scores for each personality dimensions graded according to 5-point scale, ranging from very low to very high. Statistical analysis was performed by SPSS software (version 16.0). Data were examined by t- tests, λ 2 test, Fisher's exact tests, ANOVA and Spearman's ρ correlation. A p-value <0.05 was considered significant. Results: The mean value ESSDAI score was 4.30±3.70. Comorbidity was similar in both groups (p>0.05). Scores N were significantly higher in SS patients than in healthy controls (95.4 and 79.8, respectively, p=0.001). This N scores in SS group correlates negatively with disease duration (ρ=-0.30, p=0.01). Control group had significantly higher E (107.8) and O (99.7) scores than SS group (93.0 and 99.7 respectively, p=0.00). Scores C were higher in SS patients than in control group (129.4 and 121.9), but differences were not statistically significant (p=0.06). Scores A were quite similar in both groups (p>0.05). The differences between groups were not statistically significant for psychological profiles and age, educational levels, occupational status (ANOVA, p>0.05). Scores A in SS group were significantly higher in urban population (p=0.03). Several psychological profiles were significantly related with some domens of ESSDAI (hematological, pulmo, peripheral nervous system), p<0.05. Conclusions: Our patients with SS had neurotic psychological profile and probably have increased risk to develop different mental disorders. The level of neuroticism was higher at the onset of the disease. Compared with healthy controls, SS patients are more introverted and conservative, less opened and similarly agreeable and conscientious to healthy controls. Correlation of certain psychological profiles of SS patients and disease activity is questionable. Disclosure of Interest: None declared